2000
DOI: 10.1002/1098-2736(200011)37:9<895::aid-tea3>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Culture wars in the classroom: Prospective teachers question science

Abstract: Does studying about the nature(s) of science contribute to a prospective teachers' effectiveness as a science teacher? This research grew out of a course created by a science educator and historian of science who believed prospective teachers needed more complex understandings of the cultural wars surrounding science. The research team consisted of five prospective teachers who participated in the course as well as the two instructors. This paper describes the experience of participating in the course from bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Other studies-most of which involve preservice elementary teachers-focused more squarely on experiences in science (Howes, 2002;Hynd, Alvermann, & Qian, 1997;Powell, 1994;Smith, 2000;Smith & Anderson, 1999;Sullenger et al, 2000). For example, Smith and Anderson differentiated among the 9 preservice elementary teachers in their study, characterizing them as either "knowers" of or "wonderers" about science.…”
Section: Experiences and Academic Preparation In Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…Other studies-most of which involve preservice elementary teachers-focused more squarely on experiences in science (Howes, 2002;Hynd, Alvermann, & Qian, 1997;Powell, 1994;Smith, 2000;Smith & Anderson, 1999;Sullenger et al, 2000). For example, Smith and Anderson differentiated among the 9 preservice elementary teachers in their study, characterizing them as either "knowers" of or "wonderers" about science.…”
Section: Experiences and Academic Preparation In Sciencementioning
confidence: 99%
“…A few studies investigated preservice teachers' attitudes toward science (Cobern & Loving, 2002;McDevitt, Heikkinen, Alcorn, Ambrosio, & Gardner, 1993;Settlage, 2000;Smith, 2000;Sullenger et al, 2000). One study found that, in the sample of the almost 700 elementary preservice teachers surveyed, there was "no hint" (p. 1027) of an anti-science attitude in which science is viewed negatively; rather, the authors argue, the preservice teachers' attitudes toward science were complex, reasonable, and justified (Cobern & Loving, 2002).…”
Section: Knowledge and Beliefs About Science And The Nature Of Sciencementioning
confidence: 99%